A multicentre cross-sectional clinical study on female sexual dysfunction in postmenopausal Chinese women. (June 2023) - Ju, Rui; Ruan, Xiangyan; Yang, Yu; Xu, Xin; Cheng, Jiaojiao; Bai, Yongtao; Shi, Yanhong; Yang, Xingzi; Li, Ruiling; Mueck, Alfred O.
Highlights: Female sexual dysfunction is one of the most common symptoms in aging women. The relationship between serum androgen levels and female sexual dysfunction is controversial. Liquid chromatography mass spectrometry is the best way to assess serum androgens. The intensity of climacteric symptoms significantly affects women's sexual function. A low education level was found to be a risk factor for female sexual dysfunction in China. Abstract: Objective: The aim of this study was to investigate the factors affecting the sex lives of postmenopausal Chinese women, especially the influence of body weight, climacteric symptoms and androgens. Methods: A total of 437 postmenopausal women were investigated in the Department of Gynecological Endocrinology, Beijing Obstetrics and Gynecology Hospital, Capital Medical University and two allied medical institutions from April 2020 to March 2021. Sociodemographic data were collected. Female sexual dysfunction was evaluated using the Female Sexual Function Index (FSFI). The modified Kupperman index was used to assess climacteric symptoms. Methods based on liquid chromatography-tandem mass spectrometry were employed to measure the serum levels of total testosterone, bioavailable testosterone, free testosterone, androstenedione and dehydroepiandrosterone. Pearson's correlation coefficient and multiple linear regression analyses were performed to determine the correlation between characteristics and FSFI scores. Results: The multivariate linear regression analysis revealed that the modified Kupperman index score and the factor unsatisfactory marital relations had the strongest negative correlations with all FSFI domains (P < 0.05); secondary education level was negatively associated with desire, arousal and orgasm (P < 0.05). Total testosterone positively affected the score for pain (P < 0.05). There was no correlation between bioavailable testosterone, free testosterone, androstenedione and dehydroepiandrosterone and all FSFI domains (P > 0.05). Conclusion: Climacteric symptoms and sociodemographic factors had a notable effect on sexual function. It is necessary to provide more attention to and intervention for their climacteric symptoms to improve the quality of life of postmenopausal women.